Randomized Clinical Trial of Weekly vs. Triweekly Cisplatin-Based Chemotherapy Concurrent With Radiotherapy in the Treatment of Locally Advanced Cervical Cancer - Ryu, Sang-Young; Lee, Won-Moo; Kim, Kidong; Park, Sang-Il; Kim, Beob-Jong; Kim, Moon-Hong; Choi, Seok-Cheol; Cho, Chul-Koo; Nam, Byung-Ho; Lee, Eui-Don (International journal of radiation oncology, biology, physics, 2011)
To compare compliance, toxicity, and outcome of weekly and triweekly cisplatin administration concurrent with radiotherapy in locally advanced cervical cancer. In this open-label, randomized trial, 104 patients with histologically proven Stage IIB–IVA cervical cancer were randomly assigned by a computer-generated procedure to weekly (weekly cisplatin 40 mg/m2, six cycles) and triweekly (cisplatin 75 mg/m2 every 3 weeks, three cycles) chemotherapy arms during concurrent radiotherapy. The difference of compliance and the toxicity profiles between the two arms were investigated, and the overall survival rate was analyzed after 5 years. All patients tolerated both treatments very well, with a high completion rate of scheduled chemotherapy cycles. There was no statistically significant difference in compliance between the two arms (86.3% in the weekly arm, 92.5% in the triweekly arm, p > 0.05). Grade 3–4 neutropenia was more frequent in the weekly arm (39.2%) than in the triweekly arm (22.6%) (p = 0.03). The overall 5-year survival rate was significantly higher in the triweekly arm (88.7%) than in the weekly arm (66.5%) (hazard ratio 0.375; 95% confidence interval 0.154–0.914; p = 0.03). Triweekly cisplatin 75-mg/m2 chemotherapy concurrent with radiotherapy is more effective and feasible than the conventional weekly cisplatin 40-mg/m2 regimen and may be a strong candidate for the optimal cisplatin dose and dosing schedule in the treatment of locally advanced cervical cancer.